GPx4, Lipid Peroxidation, and Cell Death: Discoveries, Rediscoveries, and Open Issues - Maiorino, Matilde; Conrad, Marcus; Ursini, Fulvio (Antioxidants & redox signaling, 2018)
Iron-dependent lipid peroxidation is a complex oxidative process where phospholipid hydroperoxides (PLOOH) are produced in membranes and finally transformed into a series of decomposition products, some of which are endowed with biological activity. It is specifically prevented by glutathione peroxidase 4 (GPx4), the selenoenzyme that reduces PLOOH by glutathione (GSH). PLOOH is both a product and the major initiator of peroxidative chain reactions, as well as an activator of lipoxygenases. α-Tocopherol both specifically breaks peroxidative chain propagation and inhibits lipoxygenases. Thus, GPx4, GSH, and α-tocopherol are integrated in a concerted anti-peroxidant mechanism. Recent Advances: Ferroptosis has been recently identified as a cell death subroutine that is specifically activated by missing GPx4 activity and inhibited by iron chelation or α-tocopherol supplementation. Ferroptosis induction may underlie spontaneous human diseases, such as major neurodegeneration and neuroinflammation, causing an excessive cell death. The basic mechanism of ferroptosis, therefore, fits the features of activation of lipid peroxidation. Still lacking are convincing proofs that lipoxygenases are involved in ferroptosis. Also, unknown are the molecules eventually killing cells and the mechanisms underlying the drop of the cellular anti-peroxidant capacity. Molecular events and mechanisms of ferroptosis to be unraveled and validated on animal models are GPx4 inactivation, role of GSH concentration, increased iron availability, and membrane structure and composition. This is expected to drive drug discovery that is aimed at halting cell death in degenerative diseases or boosting it in cancer cells. Antioxid. Redox Signal. 29, 61-74.